Cover Feature: Role of V and W Sites in V2O5−WO3/TiO2 Catalysts and Effect of Formaldehyde during NH3−SCR of NOx (ChemCatChem 15/2022). Issue 15 (13th July 2022) - Binh Ngo, Anh; Huyen Vuong, Thanh; Atia, Hanan; Weiß, Jana; Rabeah, Jabor; Armbruster, Udo; Brückner, Angelika
Abstract : The Cover Feature illustrates the effect of different sites in V2 O5 ‐WO3 /TiO2 catalysts on the conversion of NOx and HCHO in vehicle exhaust gas. In their Research Article, A. Brückner and co‐workers show that two vanadyl sites coexist in those catalysts. Only the highly redox‐active V‐O‐W moiety can convert NOx completely to eco‐friendly N2 and H2 O. Unfortunately, HCHO is transformed to toxic HCN on both sites. More information can be found in the Research Article by A. Brückner and co‐workers .